Answer: 1) D. x = -0.3 and y = -3.4
2) B. [tex]y=\frac{4}{x+2}+3[/tex]
Step-by-step explanation:
1) Given equation,
[tex]y=\frac{-1.6}{x+0.3}-3.4[/tex]
For vertical asymptote,
[tex]y\rightarrow \infty[/tex]
It is possible for the given function, if the denominator = 0
⇒ x + 0.3 = 0
⇒ x = -0.3
Now, for horizontal asymptote,
[tex]x\rightarrow \infty[/tex]
By substituting this in the given equation of the function,
We get,
[tex]y=\frac{-1.6}{\infty+0.3}-3.4[/tex]
[tex]y=\frac{-1.6}{\infty}-3.4[/tex]
[tex]y=0-3.4[/tex]
[tex]y=-3.4[/tex]
Hence, the vertical and horizontal asymptote of the given function are x = -3.0 and y = -3.4 respectively.
⇒ Option D is correct.
2) If a function is defined as,
(x-h)(y-k) = a
Then (h,k) be the center of this function,
In option A,
Given function is,
[tex]y = \frac{4}{x+3}+2[/tex]
[tex]\implies y-2 = \frac{4}{x+3}[/tex]
[tex]\implies (x+3)(y-2) = 4[/tex]
⇒ The center of the function is (-3,2)
In option B,
Given function is,
[tex]y = \frac{4}{x+2}+3[/tex]
[tex]\implies y-3 = \frac{4}{x+2}[/tex]
[tex]\implies (x+2)(y-3) = 4[/tex]
⇒ The center of the function is (-2,3)
In option C,
Given function is,
[tex]y = \frac{4}{x-2}+3[/tex]
[tex]\implies y-3 = \frac{4}{x-2}[/tex]
[tex]\implies (x-2)(y-3) = 4[/tex]
⇒ The center of the function is (2,3)
In option D,
Given function is,
[tex]y = \frac{4}{x+3}-2[/tex]
[tex]\implies y+2 = \frac{4}{x+3}[/tex]
[tex]\implies (x+3)(y+2) = 4[/tex]
⇒ The center of the function is (-3,-2)
⇒ Thus, by the above explanation the function in option B has the center of (-2,3)